Rearward visibility technology in ASEAN market - Meor Said, Mior A; Mohd Sohimin, Muhammad H F; Abu Hussain, Nurulakmar; Abd Rahman, Badruzzaman; Tuan Kamaruddin, Tengku Nordayana Akma; Mohamad Jamil, Siti Nurnadilla; Balaka, Ridway; Abu Kassim, Khairil A (2019)
Recent trend in modern vehicle design tends to make thick roof pillar for stronger structure to withstand collision impact; which results in limiting rearward visibility. One of the ways to circumvent this reduced visibility is by using Rearward Visibility Technology (RVT). The objective of this review paper is to produce an overview of RVTs available in ASEAN market. RVTs in ASEAN can be categorised into classes and sub-classes: Original Equipment Manufacturer(OEM), After Market, Class I, Class III, CMS, Auto-Dim and others. It can be concluded that RVT is still in introductory phase to the ASEAN region; as RVTs only been implemented by OEMs in several models mainly in premium price range, Electric Vehicle and Sport Utility Vehicles. After market RVT products offers cost-effective prices but the performance in comparison to OEM RVT is yet to be known.